2019
DOI: 10.1155/2019/6286197
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Striatal Delivery of GDNF from Encapsulated Cells Prevents the Anatomical and Functional Consequences of Excitotoxicity

Abstract: Methods. Human ARPE-19 cells engineered to secrete high levels of the glial cell line-derived neurotrophic factor (GDNF) were encapsulated into hollow fiber membranes. The devices were implanted into the rat striatum 1 week prior to striatal quinolinic acid injections. Animals were evaluated using a battery of validated motor tests, and histology was performed to determine the extent of GDNF diffusion and associated prevention of neuronal cell loss and behavioral deficits. Results. Encapsulated cell-based deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Using a similar approach, Gloriana Therapeutics recently reported that encapsulated cells secreting GDNF reduced both behavioral and electrophysiological seizures as well as epilepsy-related anatomical changes when implanted into the hippocampus of epileptic rats [17]. Similar devices were neuroprotective in an excitotoxic rat model of Huntington's disease [18]. These recent reports not only support the basic concepts of cell encapsulation but also bode well for the use of these technologies in a wide range of human conditions.…”
Section: Towards Clinical Translationmentioning
confidence: 79%
“…Using a similar approach, Gloriana Therapeutics recently reported that encapsulated cells secreting GDNF reduced both behavioral and electrophysiological seizures as well as epilepsy-related anatomical changes when implanted into the hippocampus of epileptic rats [17]. Similar devices were neuroprotective in an excitotoxic rat model of Huntington's disease [18]. These recent reports not only support the basic concepts of cell encapsulation but also bode well for the use of these technologies in a wide range of human conditions.…”
Section: Towards Clinical Translationmentioning
confidence: 79%
“…The development of a delivery strategy is limited due to the blood-brain barrier; however, principle studies in animal models may offer new approaches including gene delivery, cell-based delivery, and also biomaterial drug delivery [61]. In the past year, several in vivo studies have been reported for neurodegenerative diseases [71,[74][75][76]. Galli et al used alginate-poly-L-lysine-alginate (APA) microcapsules and cross-linked the spheres with both Ca 2+ and Ba 2+ .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Furthermore, utilizing stem cells to deliver these neurotrophic factors may be therapeutically potent in epilepsy. GDNF-releasing ARPE-19 cells were transplanted in quinolinic acid rats, a model of Huntington’s disease ( Emerich et al, 2019 ). Treatment resulted in effective GDNF permeation throughout the rat striatum ( Emerich et al, 2019 ).…”
Section: The Efficacy Of Stem Cells In Alleviating the Neuropsychiatrmentioning
confidence: 99%
“…GDNF-releasing ARPE-19 cells were transplanted in quinolinic acid rats, a model of Huntington’s disease ( Emerich et al, 2019 ). Treatment resulted in effective GDNF permeation throughout the rat striatum ( Emerich et al, 2019 ). GDNF ameliorated behavioral impairments and functioned to maintain healthy striatal size ( Emerich et al, 2019 ).…”
Section: The Efficacy Of Stem Cells In Alleviating the Neuropsychiatrmentioning
confidence: 99%